Preclinical evaluation of methotrexate-loaded polyelectrolyte complexes and thermosensitive hydrogels as treatment for rheumatoid arthritis - Agostini, Sandra Barbosa Neder; Malta, Iago Henrique Silva; Rodrigues, Rafaela Figueiredo; Freitas, Jennifer Tavares Jacon; Lino, Mônica Esselin de Sousa; dos Santos, Rafaela Silva; Elisei, Lívia Silvestre; Moraes, Thamyris Reis; Giusto, Luana Aparecida dos Reis; de Oliveira, Merelym Ketterym; Bassi da Silva, Jéssica; Bruschi, Marcos Luciano; et al. (Elsevier, 2021)
This work proposes new methotrexate (MTX) loaded drug delivery systems (DDS) to treat rheumatoid arthritis via the intra-articular route: a poloxamer based thermosensitive hydrogel (MTX-HG), oligochitosan and hypromellose phthalate-based polyelectrolyte complexes (MTX-PEC) and their association (MTX-PEC-HG). MTX-PEC showed 470 ± 166 nm particle size, 0.298 ± 0.108 polydispersity index, +26 ± 2 mV and 74.3 ± 5.8% MTX efficiency entrapment and particle formation was confirmed by infrared spectroscopy and thermal analysis. MTX-HG and MTX-PEC-HG gelled at 36.7°C. MTX drug release profile was prolonged for MTX-HG and MTX-PEC-HG, and faster for MTX-PEC and free MTX. The in vivo effect of the MTX-DDSs systems was evaluated in induced arthritis rats as single intra-articular dose. The assessed parameters were the mechanical nociceptive threshold, the plasmatic IL-1β level and histological analysis of the tibiofemoral joint. MTX-HG and MTX-PEC-HG performance were similar to free MTX and worse than oral MTX, used as positive control. All DDSs showed some irritative effect, for which further studies are required. MTX-PEC was the best treatment on recovering cartilage damage and decreasing allodynia. Thus, MTX-PEC demonstrated potential to treat rheumatoid arthritis, with the possibility of decreasing the systemic exposure to the drug.
Keywords: Chitooligosaccharide; Chitosan; Drug delivery system; Hypromellose phthalate; Methotrexate; Polyelectrolyte complexes; Rheumatoid arthritis